Information Processes for the Formation of a Digital State in the Republic of Tajikistan - Jami B. Chiniev (Informaciâ i Innovacii, 2019)
The article presents the author’s analysis of the process of forming elements of a digital state in the Republic of Tajikistan. The necessity of this process, its stages, and current state are grounded. The author identifies the main problems hampering the formation of a digital state in Tajikistan, the most important of which is the insufficient qualification of personnel. The author proposes a set of measures to improve the situation, among which is the intensification of cooperation with the EAEU countries in the process of formation of a digital state in Tajikistan based on common standards and requirements.